2022
DOI: 10.1111/jonm.13716
|View full text |Cite
|
Sign up to set email alerts
|

Parental experience of transition from a paediatric intensive care unit to a general ward: A qualitative study

Abstract: Aim We aim to explore parental experience in transitioning from a paediatric intensive care unit to a general ward and to investigate parental involvement in caring for their critical illness children. Background Parents have a major responsibility in caring for seriously ill children, but nursing staff fail to meet the expectations of parents regarding nursing care. Few studies have investigated the challenges and needs of Chinese parents during the transition from paediatric intensive care unit to general wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Hence, follow-up plans should be individualized to cater to the specific needs of each child. 8 , 9 Several PICU doctors in the present study believed that the post-PICU follow-up was impractical due to clinical practice, feasibility, and resources available, while some ward doctors perceived that a comprehensive assessment of the child’s high-risk factors could determine whether follow-up is needed after the PICU stay. Several studies have shown that follow-up visit has a positive impact both on patient outcomes and on the ability of healthcare professionals to improve their transitional care skill.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Hence, follow-up plans should be individualized to cater to the specific needs of each child. 8 , 9 Several PICU doctors in the present study believed that the post-PICU follow-up was impractical due to clinical practice, feasibility, and resources available, while some ward doctors perceived that a comprehensive assessment of the child’s high-risk factors could determine whether follow-up is needed after the PICU stay. Several studies have shown that follow-up visit has a positive impact both on patient outcomes and on the ability of healthcare professionals to improve their transitional care skill.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, another study exploring the experiences of parents found that doctors failed to inform parents about post-treatment plans and transition details during discharge. 8 Mueller et al 34 found that shared electronic health records and clear communication chains were considered possible solutions to improve information exchange fidelity. At the same time, shared decision-making helps patients to understand information about the treatment process and can reduce information asymmetry between doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations